Association of Thrombocytopenia in Pregnant Women with COVID-19 Vaccination in the Post-COVID Era - Sultan, Kainat; Khan, Saba; Tariq, Simrah; Maaz, Muhammad; Shahmina; Akhund, Ilqa Ikram (Indus Journal of Bioscience Research, 2025)
Background: Thrombocytopenia is the second most frequent haematological abnormality in pregnancy, up to 10% of pregnant patients, and it often concerns general practitioners. Following the introduction of mass vaccination against COVID-19, fears have been raised about potential association between COVID-19 vaccination and haematological complications, including thrombocytopenia. There is limited information on the safety of COVID-19 vaccines during pregnancy, especially in low- and middle-income countries, despite global vaccination campaigns. Objective: To explore the link between thrombocytopenia in pregnancy and the COVID-19 vaccine in the COVID-19 era. Methodology: This case control study was carried out at the Department of Gynaecology and Obstetrics, JPMC, Karachi for duration of six months. A sample of 189 pregnant women, aged >20 weeks gestation, were recruited based on non-probability consecutive sampling. Subjects were stratified according to vaccination and had thrombocytopenia defined (platelet counts <150×10⁹/L). The proformas were filled and the data analysed using SPSS software version 20. Categorical variables were compared with Chi-square or Fisher’s exact test, and a p ≤ 0.05 was considered significant. Results: Of the 189 participants, 132 (69.8%) and 57 (30.2%) were vaccinated and unvaccinated respectively. Thrombocytopenia occurred in 68 women (36%), and was significantly more common in vaccinated versus unvaccinated women (39·4% vs 28·1%, p=0·04). Of the thrombocytopenic vaccinated women, 44.2% had been vaccinated with mRNA vaccines, 34.6% with viral vector vaccines and 21.2% with inactivated virus vaccines. The majority of cases were benign and resolved after delivery with no significant complications. There were no cases of maternal mortality or perinatal loss reported. Conclusion: A significant relationship was detected between COVID-19 vaccination and thrombocytopenia in pregnant women. Although most cases were of mild clinical presentation, these observations underscore the importance of intensive antenatal assessment in vaccinated individuals and the need for other large case series.